Systematic Review of Stem Cells in Plastic, Reconstructive, and Aesthetic Surgery: Clinical Application in Anti-Aging Medicine - Napoleon, Huntal; Djohan, Putra B.; Evelyn, Evelyn; Lypinsky, Laveda; Luziani, Stefani; Margaretha, Magistra C. (Indian Journal of Plastic Surgery, 2025)
The application of stem cells in plastic, reconstructive, and aesthetic surgery has emerged as a promising frontier in anti-aging medicine. Stem cells, particularly adipose-derived stem cells (ADSCs) and mesenchymal stem cells (MSCs), are increasingly utilized for their regenerative properties, offering innovative solutions for a range of aesthetic and reconstructive challenges.This review explores the current and potential clinical applications of stem cells in plastic surgery, focusing on their role in grafting, facial rejuvenation, wound healing, soft tissue reconstruction, and hair restoration.A comprehensive literature analysis was conducted using the PRISMA algorithm, examining studies and clinical trials that evaluate the efficacy, safety, and outcomes of stem cell-based therapies in plastic surgery. Emphasis was placed on the therapeutic mechanisms of stem cells, including their ability to enhance tissue regeneration, reduce scarring, and improve graft survival.Out of the 5,117 studies identified, 22 met the inclusion criteria, highlighting the diverse applications of stem cells in plastic surgery. These studies reported significant advancements in aesthetic and reconstructive outcomes.Stem cell therapies represent a transformative approach in plastic surgery, offering significant benefits in aesthetic enhancement and functional restoration. While current applications show promising results, ongoing research is essential to address regulatory issues, ethical considerations, and the need for standardized treatment protocols.
Keywords: stem cells; plastic surgery; anti-aging; facial rejuvenation; wound healing; soft tissue reconstruction; cartilage regeneration; hair restoration